THEORETICAL FOUNDATIONS AND PEDAGOGICAL SIGNIFICANCE OF DEVELOPING PROFESSIONAL COMPETENCE - Qilichova Zarifa Xayrullo qizi (International Journal of Literature and Language Studies, 2026)
The article analyzes the concept of professional competence, its structural components, and its significance in pedagogical activity. Furthermore, the scientific views of domestic and foreign scholars on the development of professional competence will be studied, and the role of the competency-based approach in the modern education system will be highlighted. The results of the study show that professional competence is an integrated set of professional knowledge, skills, abilities, and personal qualities of a specialist.